Discovery of potent benzoxaborole inhibitors against SARS-CoV-2 main and dengue virus proteases - Kühl, Nikos; Lang, Johannes; Leuthold, Mila; Klein, Christian D. (European journal of medicinal chemistry, 2022)
The RNA viruses SARS-CoV-2 and dengue pose a major threat to human health worldwide and their proteases (Mpro; NS2B/NS3) are considered as promising targets for drug development. We present the synthesis and biological evaluation of novel benzoxaborole inhibitors of these two proteases. The most active compound achieves single-digit micromolar activity against SARS-CoV-2 Mpro in a biochemical assay. The most active substance against dengue NS2B/NS3 protease has submicromolar activity in cells (EC50 0.54 μM) and inhibits DENV-2 replication in cell culture. Most benzoxaboroles had no relevant cytotoxicity or significant off-target inhibition. Furthermore, the class demonstrated passive membrane penetration and stability against the evaluated proteases. This compound class may contribute to the development of antiviral agents with activity against DENV or SARS-CoV-2.
Gesehen am 08.11.2022